Inside Cover. Issue 4 (12th April 2021) - Won, Jungeun; Porter, Ryan G.; Novak, Michael A.; Youakim, Jon; Sum, Ada; Barkalifa, Ronit; Aksamitiene, Edita; Zhang, Anqi; Nolan, Ryan; Shelton, Ryan; Boppart, Stephen A.
Abstract: Air pressure‐driven movements of the eardrum were captured with a handheld probe‐based OCT system. The pneumaticdriven stiffness and time lag were compared between the normal ear and the ear with a middle ear infection. Further details can be found in the article by Jungeun Won, Ryan G. Porter, Michael A. Novak, Jon Youakim, Ada Sum, Ronit Barkalifa, Edita Aksamitiene, Anqi Zhang, Ryan M. Nolan, Ryan L. Shelton, and Stephen A. Boppart (e202000215 ). Abstract : Air pressure‐driven movements of the eardrum were captured with a handheld probe‐based OCT system. The pneumaticdriven stiffness and time lag were compared between the normal ear and the ear with a middle ear infection. Further details can be found in the article by Jungeun Won, Ryan G. Porter, Michael A. Novak, Jon Youakim, Ada Sum, Ronit Barkalifa, Edita Aksamitiene, Anqi Zhang, Ryan M. Nolan, Ryan L. Shelton, and Stephen A. Boppart (e202000215 ).